2015
DOI: 10.1007/s00210-015-1189-z
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine enhances the antidepressant-like activity of common antidepressant drugs in the forced swim test in mice

Abstract: Caffeine is the most widely used behaviorally active drug in the world which exerts its activity on central nervous system through adenosine receptors. Worrying data indicate that excessive caffeine intake applies to patients suffering from mental disorders, including depression. The main goal of the present study was to evaluate the influence of caffeine on animals’ behavior in forced swim test (FST) as well as the effect of caffeine (5 mg/kg) on the activity of six typical antidepressants, such as imipramine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 57 publications
3
40
0
2
Order By: Relevance
“…Immobility was defined as the time the mouse spent floating in the water without struggling or only making those movements required to keep its head above the water. Conventional antidepressant drugs can decrease the immobility time in this test (20).…”
Section: Introductionmentioning
confidence: 91%
“…Immobility was defined as the time the mouse spent floating in the water without struggling or only making those movements required to keep its head above the water. Conventional antidepressant drugs can decrease the immobility time in this test (20).…”
Section: Introductionmentioning
confidence: 91%
“…Caffeine is one of the most frequently used psychoactive substances ingested mainly via beverage products and some foods by millions of people around the world. Recently, it was evidenced that caffeine enhanced the antidepressant‐like activity of six typical antidepressants including imipramine, desipramine, fluoxetine, paroxetine, escitalopram, and reboxetine in the forced swim test in mice . Moreover, the anxiogenic and helpless‐like behavior and decreased memory performance induced by chronic unpredictable stress were prevented by caffeine administration .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous in‐vivo studies, we showed that caffeine, a non‐selective inhibitor of the adenosine receptors, not only exerted by itself an antidepressant‐like activity in the FST and the TST in mice when given acutely, but also potentiated the effect of antidepressant drugs belonging to different pharmacological groups . It is generally known that caffeine antagonizes all four adenosine receptor subtypes and also acts as a phosphodiesterase inhibitor; therefore, the observed results could have been a resultant of this multiway antidepressant mechanism of action.…”
Section: Introductionmentioning
confidence: 82%